2001
DOI: 10.1093/intimm/13.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by the antigen receptor and Fas in a variant of the immature B cell line WEHI-231 and in splenic immature B cells

Abstract: Signaling by the BCR causes proliferation and resistance to Fas-induced apoptosis in mature B cells, but growth arrest and apoptosis in immature B cells. We have identified a variant of the immature B cell line WEHI 231 that retains the apoptotic response to the BCR but has acquired susceptibility to Fas-induced apoptosis. The Fas susceptibility was associated with increased Fas expression on the cell surface and down-regulated IgD expression. These cells exhibited a distinctive functional relationship in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Consistent with our result, immature splenic B cells are insensitive to Fas triggering [28]. In contrast to FLIP, Tg expression of Bcl-2 restored B cell maturation and function in TACI-Ig-Tg mice, as judged by the rescue of mature lymph node B cells and the ability to mount a Tdependent antibody response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our result, immature splenic B cells are insensitive to Fas triggering [28]. In contrast to FLIP, Tg expression of Bcl-2 restored B cell maturation and function in TACI-Ig-Tg mice, as judged by the rescue of mature lymph node B cells and the ability to mount a Tdependent antibody response.…”
Section: Discussionsupporting
confidence: 91%
“…TACI-Ig-Tg mice immunized with the T-dependent model antigen NP 28 -chicken gamma globulin (NP-CGG) had a severely impaired anti-NP humoral response, consistent with their deficit in mature B cells. In contrast, TACI-Ig×Bcl-2 dTg mice readily mounted T-dependent humoral responses, indicating that expression of Bcl-2 rescues not only the presence but also the function of B cells (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Studies performed with transformed and primary immature sIg ϩ B cells have begun mapping apoptosis pathways invoked during clonal deletion (Wu et al, 1996a(Wu et al, , 1998Andjelic and Liou, 1998;Doi et al, 1999;Ruiz-Vela et al, 1999;Tian et al, 2001). Our previous studies with nontransformed, bone marrow stromal cell-dependent, primary pre-B cells and pro-/pre-B cell lines have shown that a similar but clearly distinct set of events leads to apoptosis at an earlier stage of B cell development when cultures are exposed to immunosuppressive environmental chemicals (Yamaguchi et al, 1997a;Mann et al, 1999Mann et al, , 2001Ryu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the signaling pathway leading to immature B cell death and clonal deletion has been mapped in model systems in which transformed cells (e.g., WEHI-231) (Wu et al, 1996a(Wu et al, , 1998Andjelic and Liou, 1998;Doi et al, 1999;Ruiz-Vela et al, 1999) or immature splenic B cells (Andjelic and Liou, 1998;Tian et al, 2001) were induced to undergo apoptosis after immunoglobulin cross-linking. In these systems, contributions of nuclear factor-B and c-Myc down-regulation (Wu et al, 1996a,b);p53, p27 Kip1 , and p21 WAF1 up-regulation (Wu et al, 1998); mitochondrial activation (Doi et al, 1999); and protease (calpain, cathepsin, and caspase) activation (Ruiz-Vela et al, 1999) have begun to be defined.…”
mentioning
confidence: 99%
“…Considering that Fas expression not necessarily correlate with Fas-mediated apoptosis susceptibility [32] and that B cells from aged-animals present lower Fas+ B cells than those from young mice, we examined the susceptibility of BCRstimulated B cells from aged animals to anti-Fas killing. Thus, purified splenic B cells from young and aged mice were cultured with F(ab) 2 anti-μ during 48 h, re-cultured with anti-Fas antibody or control hamster IgG during 12 h and stained with PI to determine the percentage of apoptotic cells by FCM.…”
Section: B Cells From Aged Mice Exhibit the Same Susceptibility To Anmentioning
confidence: 99%